Progress in Coupling Potential Wave Models and Two-Phase Solvers With the SWENSE Methodology - Li, Zhaobin; Bouscasse, Benjamin; GENTAZ, L.; Ducrozet, Guillaume; FERRANT, Pierre (Volume 9: Offshore Geotechnics; Honoring Symposium for Professor Bernard Molin on Marine and Offshore Hydrodynamics, 2018)
International audience This paper presents the recent developments of the Spectral Wave Explicit Navier-Stokes Equations (SWENSE) method to extend its range of application to two-phase VOF solvers. The SWENSE method solves the wave-structure interaction problem by coupling potential theory and the Navier-Stokes (NS) equations. It evaluates the incident wave solution by wave models based on potential theory in the entire computational domain, leaving only the perturbation caused by the structure and the influence of the viscosity to be solved with CFD. The method was proven in previous studies to be accurate and efficient for wave-structure interaction problems, but it was derived for single-phase NS solvers only. The present study extends the SWENSE method by proposing a novel formulation which is convenient to implement in two-phase NS solvers. A customized SWENSE solver is developed with the open source CFD package Open-FOAM. An improvement in accuracy and stability is observed in wave simulations compared with conventional two-phase VOF solvers. The horizontal force on a vertical cylinder in regular waves is also calculated. First results show a good agreement with the experiment on the first harmonic component.